Evaluation Of Physical Facilities Available At Subcentres In District Meerut - Jain Seema; Singh J.V; Bhatnagar M; Garg S.K; Chopra H; Bajpai S.K (Wolters Kluwer Medknow Publications, 1999)
Research Question: What is the status of physical facilities available at the sub-center? Objective: To assess the physical facilities available at subcentres in District Meerut. Study design: Cross-sectional Participants: 25 sub-centres Statistical Analysis: By a scoring system based on percentages. Results: All sub-centres were graded and ranked according to available physical facilities and basic amenities. Among all, 44% subcentres were graded as good and poor, 12% as average, while none of the sub-center had excellent facilities available.